Cyclin-dependent kinase 4/6 inhibitors as first-line treatment for post-menopausal metastatic hormone receptor-positive breast cancer patients: a systematic review and meta-analysis of phase III randomized clinical trials. - Ramos Esquivel, Allan Eduardo (2018)
Background To compare the efficacy and toxicity of the combination of cyclin-dependent kinase 4/6 (CDK 4/6) inhibitors and nonsteroidal aromatase inhibitors (AI) versus AI alone as first-line therapy for patients with advanced hormone receptor-positive breast cancer. Materials and methods Phase III randomized clinical trials (RCT) were identified after a systematic review of electronic databases. A random-effect model was used to determine the pooled hazard ratio (HR) for progression-free survival (PFS) using the inverse-variance method. The Mantel–Haenszel method was used to calculate the pooled odds ratio (OR) for overall response, clinical benefit rate and treatment-related side effects. Heterogeneity was measured using the tau-squared and I2 statistics. Results After a systematic search, three phase III RCT (n = 1827) were included. The use of CDK 4/6 inhibitors (abemaciclib, palbociclib, and ribociclib) in combination with an AI was significantly associated with longer PFS compared to the use of letrozole or anastrozole alone (HR: 0.57; 95% CI 0.50–0.65; p < 0.00001), with no significant heterogeneity among trials. Similarly, overall response rate and clinical benefit rate were higher for patients who received the combination therapy than for patients allocated to AI alone. Grade 3 or higher treatment-related side effects were more frequently reported for patients who received CDK 4/6 inhibitors (OR: 7.51; 95% CI 6.01–9.38; p < 0.00001), these included mainly neutropenia, leukopenia and anemia. Conclusion The addition of CDK 4/6 inhibitors (either abemaciclib, palbociclib, or ribociclib) to an AI (anastrozole or letrozole) significantly improved PFS, overall response rate, and clinical benefit rate in comparison with a nonsteroidal AI alone.